Case on System Performance Improvement - Subramaniam, Bawani; Sorooshian, Shahryar (Penerbit UMP, 2017)
Performance improvement is a formal approach to the analysis of service operations and systematic effort for improvement. System performance improvement is also an ongoing effort to make performance better which might be in industry. The aim of this case is to improvement performance of the S.M Enterprise Company which the manager based on their good location, system effort and investments believes that their performance can be much higher than the current situation.